Process Types of Transitivity System in The Ritual Teks of Tawur Sasih Kesanga in Desa Adat Kuta (e-Journal of Linguistics, 2020)
This study is aimed to analyze the process types oftransitivity system in a ritual text of Tawur Sasih Kesanga in DesaAdat Kuta. This research uses primary data contains oftranscription of a text that recorded at the ritual and a text thatrecorded when interview the ritual leader, pemangku. The datawas collected by observation method and 1-on-1 interviewmethod. The data is analyzed qualitatively and presented byapplying formal and informal methods.The result of this study indicate that there are five (5)types of transitivity processes used in the Ritual Text of TawurSasih Kesanga in Desa Adat Kuta, thore are: (1) Material processis used dominantly as many as 73 or 52,9%; (2) The use ofrelational process is found as many as 40 or 29%; (3) Behavioralprocess is used as many as 10 or 7,2%; (4) the use of mentalprocess is found as many as 8 or 5,8%; (5) The last one, it’s foundthat existential process is used as many as 7 or 5,1%.
Keywords: Translation; English Medical Terms; Translation Procedures